Influence of green finance on agricultural green total factor productivity: a case study in China - Chu, Liang; Cheng, Liang; Gao, Yulong; Deng, Huaiyue; Wang, Qian; Luo, Yaqiang (Frontiers in Environmental Science, 2024)
With the widespread promotion of the concept of green development, China’s green credit policy system has been established, developed, and gradually improved during the past decade. Against the background of the country’s vigorous development of green finance, this finance has had an increasingly important influence on agricultural green total factor productivity (GTFP). In this study, we took 30 provinces (autonomous regions or municipalities directly under central government control) in China as research samples (Hong Kong, Macao, Taiwan, and Tibet were not included due to a lack of data). The time period from 2010 to 2020 was selected as the research period, given that 2010 was the year when the development stage of China’s green finance was first initiated. Through in-depth analysis of the spatial correlations of agricultural GTFP in China and the influences of green finance on agricultural GFTP, we constructed a research framework with multiple dimensions, including green credit, green bonds, green insurance, green investment, and carbon finance. We then systematically studied the influences of green finance on agricultural GTFP. Our results showed that: (1) The development levels of green finance and agricultural GTFP in China were high, but there were not able differences among provinces, with higher agricultural GTFP in northern China and lower agricultural GTFP in central China; (2) green finance had the greatest promoting effect in western China, a weaker promoting effect in central China, and the weakest promoting effect in eastern China; and (3) green finance can indirectly promote improvements in agricultural GTFP by promoting the upgrading of industrial structure, driving technological progress, and optimizing energy consumption structure. Our work not only provides valuable reference data and suggestions for the green and sustainable development of China’s agriculture but also academic support for the development of China’s agricultural economy.